From Kampungs to Condos? Contested accumulations through displacement in Jakarta. (March 2018) - Leitner, Helga; Sheppard, Eric
Across cities of the global South, major initiatives are underway to assemble land from informal settlements in order to make it available for large-scale infrastructure and commercial real estate projects. Driven by global city aspirations, profit-seeking developers, demands from emergent middle classes for modern residential, consumption and recreational spaces, and, last but not least, the availability of finance, these land transformations seek to commodify and enclose residential urban commons and involve the displacement of thousands of urban residents. Through an examination of two field sites, a 'legal' kampung where land is being acquired through negotiations between kampung residents with land rights and developers' land brokers, and two 'illegal' kampungs whose residents were evicted in the name of flood mitigation, we conclude that the default theory for explaining these processes—accumulation by dispossession—is inadequate for capturing the variegated and complex nature of such processes. By thinking through Jakarta, we seek to provincialize the dominant concept of accumulation by dispossession, proposing an extension that we suggest is better attuned to capture the distinct features of Southern cities: Contested accumulations through displacement.